2019
DOI: 10.1097/ajp.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Pain Modulation in Chronic Low Back Pain

Abstract: Objective: The objective of the review is to determine whether conditioned pain modulation (CPM) is impaired in adults with chronic low back pain (CLBP) when compared with pain-free individuals. Methods: A a systematic search of the literature was undertaken using the databases: MEDLINE, Scopus, CINAHL and Web of Science. The citations of included studies were reviewed for additional studies. Observational, cross-sectional, case-control studies publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Also, we did not observe any significant differences in subjective pain measures (BPI pain severity and interference) between efficient and deficient CPM in individuals with cLBP. Our findings are consistent with recent systematic reviews that revealed a lack of strong relationship between CPM efficiency and cLBP [ 17 , 67 ]. Three additional observations from our data may support this observation: (1) more pathways were enriched in the PFC than cLBP group, (2) there was more overlap in GO and functional pathways between PFC and cLBP groups than unique cLBP pathways, and (3) the PFC group had more unique pathways than cLBP group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, we did not observe any significant differences in subjective pain measures (BPI pain severity and interference) between efficient and deficient CPM in individuals with cLBP. Our findings are consistent with recent systematic reviews that revealed a lack of strong relationship between CPM efficiency and cLBP [ 17 , 67 ]. Three additional observations from our data may support this observation: (1) more pathways were enriched in the PFC than cLBP group, (2) there was more overlap in GO and functional pathways between PFC and cLBP groups than unique cLBP pathways, and (3) the PFC group had more unique pathways than cLBP group.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, it has been suggested that enhanced pain sensitivity and deficient CPM correlate with greater cLBP severity and disability [ 16 ]. More recently, two systematic reviews found that individuals with cLBP have significantly reduced CPM [ 17 ] and pressure pain thresholds (PPTs) [ 8 ]. Thus, it is possible that nonspecific cLBP is related to alterations in descending pain modulatory pathways.…”
Section: Introductionmentioning
confidence: 99%
“…This finding implies a potential benefit to using pain duration, but a limitation in using pain intensity, to infer a participant’s pain mechanism. Multiple studies have suggested that pain intensity does not correlate strongly with QST 41–43 . A poor relationship was found between PPT and pain intensity, whereas a fair relationship was found for TS, in mixed samples with spinal pain 41 .…”
Section: Discussionmentioning
confidence: 92%
“…Regional hyperalgesia and decreased conditioned pain modulation (CPM) are indicative of CS and have been shown in subjects with whiplash‐associated disorder compared with subjects with chronic neck pain 44 . However, mixed results have been reported for using CPM in subjects with LBP, as CPM has not been shown to be a good prognostic tool for severe sciatica 43,45 . Future studies should continue to investigate the utility of testing for regional hyperalgesia, allodynia, and altered pain processing (TS or CPM) to more accurately identify alterations in central pain modulation present in subjects with chronic musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, these paradigms have been increasingly used in research to determine if individuals with chronic pain have an altered pain inhibition response. For example, some studies reported an alteration of pain inhibition in individuals with chronic low back pain (CLBP) using CPM [6][7][8][9] and EIH [10,11].…”
Section: Introductionmentioning
confidence: 99%